Aerobic and respirative growth of heterofermentative lactic acid bacteria: A screening study. (December 2018) - Zotta, Teresa; Ricciardi, Annamaria; Ianniello, Rocco G.; Storti, Livia V.; Glibota, Nicolas A.; Parente, Eugenio
Abstract: Heterofermentative lactic acid bacteria (76 strains) belonging to Lactobacillus, Leuconostoc and Weissella species which are important in fermentation, spoilage or as probiotics were screened in a factorial experiment for their ability to grow, produce catalase and consume oxygen in aerobiosis or in anaerobiosis, with or without supplementation with hemin and/or menaquinone in a medium containing glucose as a carbohydrate source. Aerobiosis improved growth with a few exceptions. The effect of supplementation with heme and/or menaquinone was strain specific and clear evidence of heme-boosted respiration was found in some cases. Heme-catalase was produced by strains of L. brevis, W. minor and Leuc. mesenteroides ; some strains of the latter species produced non-heme catalase. Shaken flasks experiments showed that aerobic growth resulted in increased maximum growth rate and in a limited increase in biomass. Heme supplementation during aerobic growth resulted in a further increase in growth rate and final biomass only for a few strains; this was often related to catalase, which was also responsible for increased tolerance of H2 O2 . In both experiments we found evidence of heme toxicity, especially in anaerobiosis and in absence of menaquinone. Dose response curves for aerobic growth in the presence of combinations of hemin and menaquinone were non-monotonic, with growth stimulation at low doses of heme (<2.5 mg/l) and toxicity at higher doses. Menaquinone at 0.25–8 mg/l increased growth stimulation and partially reduced toxicity. Highlights: Growth was improved by aerobiosis for most heterofermentative LAB strains. Heme supplementation resulted in growth stimulation in aerobiosis for some strains. Clear evidence of a respiratory phenotype was found for 22% of strains. Heme-dependent and heme-independent catalase activity was strain specific. Evidence of heme toxicity, relieved by aerobiosis and menaquinone, was found.